SOCIAL MEDIA AS A MEDIUM OF CUSTOMER ENGAGEMENT CASE STUDY FACEBOOK FORUM JUAL-BELI DI SULAWESI UTARA) - Qisthyna, Eva .; Saerang, David P.E; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Social Media is rapidly emerging as the next big frontier for customer engagement and interactions. A lot of social media users in Indonesian, businesses, and brands worldwide are strategizing marketing plans on their social channels in order to advertise and sell their products. Various kinds of business opportunities, business information, marketing strategies of a product can be found in every facebook update its users. Creativity content on facebook can be a medium of customer engagement. the purpose of this research are to analyze social media marketing creativity strategies as medium of consumer engagement, To identify a medium of customer engagement in social media creativity strategie. This study uses purposive and snowball sampling. This research highlighted the ability of social media to enable more frequent, faster, and richer interactions among groups of people. The results of this research from 10 informants from members of forum buying and seling. The findings of this study revealed that five factors have a significant impact on customer engagement: Trust in information, concern for privacy, perception of reliability, security in social media and use of social media. The more the customers viewed an organization to be trustworthy and secure, the better they would interact. For the customer or buyers, it is not a problem to do transaction, but make sure product you want to buy it is .Â Â Keywords: social media marketing, marketing creativity strategy,customer engagement.